2016
DOI: 10.1038/aps.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid analogues from Gynura nepalensis protect H9c2 cardiomyoblasts against H2O2-induced apoptosis

Abstract: Compound 6 isolated from the leaves of Gynura nepalensis potently protects H9c2 cardiomyoblasts against HO-induced apoptosis, possibly by inhibiting intrinsic apoptosis and the ERK/JNK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 39 publications
5
36
0
Order By: Relevance
“…Excessive ROS damages various biomolecules via lipid peroxidation, protein oxidation, and DNA damage, thereby causing ΔΨm collapsing, caspase-3 activation and cell apoptosis (Zhu and Zuo, 2013 ). In accordance with a previous study (Sun et al, 2011 ; Yu et al, 2016 ), our present study demonstrated that H 2 O 2 exposure remarkably increased ROS production and resulted in the disruption of ΔΨm in H9c2 cells. However, analogue 5d pretreatment significantly decreased the level of intracellular ROS production and inhibited the collapse of ΔΨm (Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…Excessive ROS damages various biomolecules via lipid peroxidation, protein oxidation, and DNA damage, thereby causing ΔΨm collapsing, caspase-3 activation and cell apoptosis (Zhu and Zuo, 2013 ). In accordance with a previous study (Sun et al, 2011 ; Yu et al, 2016 ), our present study demonstrated that H 2 O 2 exposure remarkably increased ROS production and resulted in the disruption of ΔΨm in H9c2 cells. However, analogue 5d pretreatment significantly decreased the level of intracellular ROS production and inhibited the collapse of ΔΨm (Figure 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…The percentage of viable and apoptotic cells showed a significant difference (p<0.05) compared to the control but not the percentage of necrotic cells. Our results were in agreement with previous studies which reported that H 2 O 2 induced apoptosis in several cell lines (Chen et al 2016;Jin et al 2013;Yu et al 2016). Cells pretreated with ObEA and NAC for 2 h prior to the H 2 O 2 induction increased cell viability in dose-dependent manners.…”
Section: Antioxidant and Free Radical Scavenging Activities Of O Bassupporting
confidence: 93%
“…In this study, five di- O -caffeoylquinic acids ( di-COQ ), which are distributed in different plants [ 10 , 11 , 12 , 13 , 14 ], were selected as references for the conformational effect investigation. As shown in Figure 1 , the five di-COQs comprise 1,3-di- O -caffeoylquinic acid ( 1 , 3-COQ ), 1,5-di- O -caffeoylquinic acid ( 1 , 5-COQ ), 3,4-di- O -caffeoylquinic acid ( 3 , 4-COQ ), 3,5-di- O -caffeoylquinic acid ( 3 , 5-COQ ), and 4,5-di- O -caffeoylquinic acid ( 4 , 5-COQ ).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that some of these compounds have already been explored for their antioxidant ability using a DPPH•-scavenging assay, ABTS• + -scavenging assay, anti-low-density lipoprotein (LDL) oxidation assay [ 11 , 15 ], and cellular assay [ 13 ]. However, each of these studies was based on the plant origin: Hung focused on antioxidants from Dipsacus asper , Zhang only explored antioxidants in Lonicera japonica , and Wan was only engaged in the phytochemical work of Chrysanthemum coronarium [ 14 ].…”
Section: Introductionmentioning
confidence: 99%